1994
DOI: 10.1136/jmg.31.4.293
|View full text |Cite
|
Sign up to set email alerts
|

A study of 159 Portuguese patients with familial amyloidotic polyneuropathy (FAP) whose parents were both unaffected.

Abstract: We reviewed 1233 cases of familial amyloidotic polyneuropathy (FAP) from 489 Portuguese families registered at the Centro de Estudos de Paramiloidose, Porto, Portugal. It was found that in 159 cases, neither parent had shown symptoms of this hereditary dominant form of peripheral neuropathy. These cases appear to form a distinct group, with a later age at onset (mean 45-1 years, SD 12-0) than the group of patients with one affected parent (mean 31-2 years, SD 6-9) and a geographical origin not quite in the are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 14 publications
3
47
0
4
Order By: Relevance
“…Studies of patients with FAP TTR Met30 in an endemic area of Portugal showed an age at onset and phenotype similar to early-onset FAP TTR Met30 cases in Japan 1,5,14 ; Portuguese patients without a family history showed a tendency toward later onset and a somewhat atypical geographic distribution, paralleling our findings. 27 Late-onset FAP TTR Met30 with atypical features including a low penetrance rate also was reported in English patients residing in the United States. 28 The FAP TTR Met30 in Swedish endemic foci has been reported to show a relatively late age at onset, a tendency to manifest sensory neuropathy as an initial symptom rather than autonomic manifestations, and a low rate of penetrance, 3,4,11,12 all differing from typical Japanese patients in endemic foci, possibly suggesting the influence of ethnic population-based genetic background.…”
Section: Commentmentioning
confidence: 88%
“…Studies of patients with FAP TTR Met30 in an endemic area of Portugal showed an age at onset and phenotype similar to early-onset FAP TTR Met30 cases in Japan 1,5,14 ; Portuguese patients without a family history showed a tendency toward later onset and a somewhat atypical geographic distribution, paralleling our findings. 27 Late-onset FAP TTR Met30 with atypical features including a low penetrance rate also was reported in English patients residing in the United States. 28 The FAP TTR Met30 in Swedish endemic foci has been reported to show a relatively late age at onset, a tendency to manifest sensory neuropathy as an initial symptom rather than autonomic manifestations, and a low rate of penetrance, 3,4,11,12 all differing from typical Japanese patients in endemic foci, possibly suggesting the influence of ethnic population-based genetic background.…”
Section: Commentmentioning
confidence: 88%
“…3,4 In contrast, 13% of the patients may have a negative family history. 8 In our case of FAP Val30Met without a family history, we suspected a de novo mutation of the TTR gene. However, FAP Val30Met may vary in phenotype due to varying penetrance, and may even be asymptomatic due to parental germline mosaicism.…”
Section: Discussionmentioning
confidence: 99%
“…However, FAP Val30Met may vary in phenotype due to varying penetrance, and may even be asymptomatic due to parental germline mosaicism. 5,8,9 Thus, inherited mutation of the TTR gene from asymptomatic parents could not be ruled out completely in this case because genetic testing was not performed in the parents. The disease is autosomal dominant of inheritance and the majority of the patients, our patient as well, are heterozygous for the Val30Met mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is transmitted in an autosomal dominant way, with a penetrance that approaches 100% in the areas of higher prevalence. Although TTR Val30Met mutation occurs worldwide, the largest focus is located in the north of Portugal [9,10,11]. Andrade [12] observed the first patient in 1939, and since then more than 3,700 patients have been registered at our center in Hospital Santo António, Porto.…”
Section: Introductionmentioning
confidence: 99%